2002
DOI: 10.1046/j.1439-0523.2002.730285.x
|View full text |Cite
|
Sign up to set email alerts
|

Present and future of quantitative trait locus analysis in plant breeding

Abstract: The joint analysis of genotype marker segregation and phenotypic values of individuals or lines enables the detection and location of loci affecting quantitative traits (QTL). The availability of DNA markers and powerful biometric methods has led to considerable progress in QTL mapping in plants.The most obvious applications of QTL analysis seem to be marker-assisted selection (MAS) in breeding and pre-breeding and QTL cloning. However, other areas are envisaged where QTL analysis can contribute decisively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
115
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(124 citation statements)
references
References 134 publications
4
115
0
5
Order By: Relevance
“…Interestingly, Verma et al (2004) mapped several QTL for grain yield and flag leaf senescence near the markers Xgwm30 and Xgwm539 on chromosome 2D in winter wheat, whereas in this study, three additive QTL for SWSCF and TGWM and eight loci associated with epistasis for SWSCF, TGWM, RESWC, GFEE, and GFEL were adjacent to markers Xgwm30 and Xgwm539 on chromosome 2D. In addition, phenotypic correlation analyses among these traits were found to be similar in our work and previous studies (Yang et al 2000;2002;Yang and Zhang 2006). It was hypothetical that the genetics of SWSC content, SWSC remobilization, grain filling, grain yield, and leaf senescence could be related.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, Verma et al (2004) mapped several QTL for grain yield and flag leaf senescence near the markers Xgwm30 and Xgwm539 on chromosome 2D in winter wheat, whereas in this study, three additive QTL for SWSCF and TGWM and eight loci associated with epistasis for SWSCF, TGWM, RESWC, GFEE, and GFEL were adjacent to markers Xgwm30 and Xgwm539 on chromosome 2D. In addition, phenotypic correlation analyses among these traits were found to be similar in our work and previous studies (Yang et al 2000;2002;Yang and Zhang 2006). It was hypothetical that the genetics of SWSC content, SWSC remobilization, grain filling, grain yield, and leaf senescence could be related.…”
Section: Discussionsupporting
confidence: 85%
“…Phenotypic plasticity of quantitative traits arises in nature from interactions between QTL and environments at molecular levels. Several examples of QEIs for agronomic traits showed that the expression of particular chromosome regions differs across environments (Crossa et al 1999;Hemamalini et al 2000;Asíns 2002;Campbell et al 2003). In this study, in addition to identifying the additive and epistatic QTL, A-QEIs and E-QEIs for all nine traits were also detected.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Several factors have an important influence on the accuracy of QTL analysis (Asins 2002), including population size and experimental design. In the present study, 7 populations with over1000 lines were used to map the QTLs controlling KD.…”
Section: Penamentioning
confidence: 99%
“…O VER the past decade, marker-assisted selection has become a standard tool in breeding programs (Young 1999;Asins 2002;Dekkers and Hospital 2002;Collard et al 2005). The selection of genetically superior individuals using molecular marker alleles linked to quantitative trait loci (QTL) affecting trait variation instead of using phenotypic trait values can speed up genetic improvement considerably (Hospital et al 1997).…”
mentioning
confidence: 99%